Bibliographical databases as a learning support in the improvement of research skills in university students of a public university - García Dávila , Mabel Beatriz (2024)
In the present research, the general objective was to determine whether bibliographic databases were a learning support to improve research skills in university students, so the methodology applied was quantitative, non-experimental, the data collection was cross-sectional and correlational analysis, which sought to determine the correlations between the study variables and complemented by means of SPSS v.28. In the processing of results between bibliographic databases and research skills, it was shown that there is a high positive correlation between bibliographic databases as a learning support and the improvement of research skills. It is important to highlight that each of the studied dimensions of the independent variable such as reliability, support, quality and accessibility of the information showed a positive relationship in the improvement of the research skills of the students who were part of the inquiry, highlighting the quality of information with a high positive correlation in the research skills where the quality of information is substantially based on the rigor, originality, clarity and updating of information provided by these databases and which improve the practical, communication and information search strategy skills, The results showed that p<0.05 and rho=0.744, therefore it is concluded that there is a high positive relationship between organizational barriers and the accreditation process. Therefore, it is concluded that bibliographic databases support and strengthen research skills.